Market Potential of Freshwater Fish Farmers in Limpopo Province - Maebane, Master; Manchidi, Ntise; Chiloane-Phetla, Germinah (Journal of Economics and Behavioral Studies, 2022)
O. mossambicus is one of the most cultured food fish worldwide. In sub-Saharan Africa, it is essential for meeting the need for food security, as it can be a cheap source of protein. Previous studies focused to some extent on the profitability of tilapia farmers. This study aims to make a scientific contribution by analyzing the market environment, and specifically the potential customers, of the O. mossambicus farmers who belong to small and medium enterprises in agriculture, by using a feasibility analysis framework. A mixed-methods approach was used to achieve the research objectives. Data were analyzed using the Statistical Package for the Social Sciences (SPSS), to compile descriptive and inferential statistics. The reliability and validity of the data collection instrument were measured using Chronbach’s Alpha values. One-way analysis of variance (ANOVA) was the statistical method used, and the f-test was conducted to determine the statistical significance of the variables in the multivariate analysis. The overall results of the study showed that O. mossambicus farmers largely sell the fish fresh to individual consumers and informal fish traders at farm stalls. In contrast, fish traders bought the O. mossambicus frozen or smoked from other suppliers. Here, recommendations are made in respect of new entrepreneurial ventures, next steps for business consultants and other stakeholders in the O. mossambicus industry, and future research directions.